Internação hospitalar e trauma : evento sentinela para monitoramento dos efeitos das drogas de abuso - Santana, Cleiton José (2015)
As there is no effective epidemiological surveillance process for measurement of intoxication and the effects of drugs of abuse in population's health developed in health local systems through active and passive monitoring system, discrete data are used to point prevention and care intervations. The concept of sentinel events was defined by Rutstein and researchers as the occurrence of illness, invalidity or unnecessary and preventable death through primary care actions, making clear-cuts rates to quality health care. The formation of sentinel events surveillance systems aims to monitor key indicators in general population or in special groups that serve as an precocious warning for the system, eliminating the concern with accurate estimates of incidence or prevalence in general population. The sentinel event Hospitalization with diagnostic of trauma associated to intoxication by drugs of abuse was created for active epidemiological surveillance of the harm, considering hospitalization for trauma as avoidable and an indicator of severity of living conditions of life and health care of patients who should have been assisted by public policies for drug abuse. The exploratory-descriptive study, developed in Maringa, state of Parana, Brazil, aimed to analyze the sentinel event to develop a surveillance system of the effects of drug abuse in users' health and its consequences in their families. This investigation was made according to epidemiological and clinical patterns, document analysis and family interview, with cases from a center of information and toxicological assistance named Center of Toxicological Assistance at University Hospital of Maringa-HUM. The study was composed of 30 family members of patients hospitalized in University Hospital of Maringa - HUM from April to September 2014. Toxicological Occurance Form of Alcoholic Intoxication and/or other Drugs of Abuse (OT/IA) and the list of inpatients and their records were used as data source. The data collection instruments used were the Epidemiological Investigation Route of Sentinel Events, the Patient's Clinical Evaluation Route and the logbook, organized by the researcher. The data collection procedure followed the investigation method of sentinel events, expanded with clinical evaluation of cases. The socialdemographic characterization data of the family member interviewed, of the sentinel event and the sentinel family were united in a spread sheet in Microsoft Office Excel Software 10.0, with presentation of absolute and relative frequency and calculating the avarage and standard deviation. For clinical classification of events were analyzed the percentage of responses to items of the neurological assessment scales of Glasgow and Reed and the evaluation of intoxications severity, and scaled their scores. The matrix to evaluate the cases followed root cause analyses model, with adjustment proposed in London Protocol by Seeking out the underlying root causes of events - SOURCE. All etchical aspects involved in the research were rigorously executed (Register number 458.185). The profile of users indicated predominance of males, ages between 13 and 65 years and avarage 40,1 years, low education level and unemployment. The most used drug was alcohol, isolated or associated to other drugs and half of the users use tem daily. The caracterization of sentinel event indicated 73,4% of cases in external environment, mostly traffic accidents, falls and physical agression. The Intoxicated Patient's Clinical Evaluation scored five (16,6%) with visible to severe symptoms, life-threatening and a fatal case; in 18 cases (60,0%) there was a polytrauma register and in 11 (36,6%) behavioral and psychomotor alterations. The reason for starting doing drugs rmentioned by the family in 18 cases (60%) was the influence of friends, and in 17 cases (56,8%) the family dicovered the use immediately because of the user's behavior alteration in family context. The similarities and differences of sentinel events were related to user contexto of life and his family. There were reports of violence during childhood, previous traumas, illicit processes to acquire drugs, behavior alterations at home, and addictive behavior in families (42%) and in 20 % of the families the use of drugs happened inside the house. Critical points were identified due to an investigation directed to occurence path of the event, which allowed the critic about public policy performance. Inadequate or deficient connection between education policy, public security, social assistance, economics and health seem to define in investigated cases the root cause of the use of drugs of abuse.